Archéologie et histoire du Sinnamary du xviie au xxe s. (Guyane) - Puaux, Olivier (Documents d'archéologie française, 1997)
The construction of the dam at Petit Saut by Électricité de France in the French Guyane gave place to an important archaeological rescue operation. Carried out from 1990 to 1995, this was the largest ever programme for an overseas French department of which the history was scarcely known. This volume represents the results of these researches in the Sinnamary river basin for the last four centuries of our millenium. Based on archives, travellers tales, old maps and archaeological work, this study brings new elements to the history of this part of South America : the formation of the colony during the 17th and 18th centuries, its settlement, its economy and material culture. With the development of gold production from the 19th century, the Guyane appears to be another California. The jail at Saut Tigre was created in 1933 for Indochinese prisoners who worked on development projects in the Inini territory up until 1944. This work contains an important dictionary of place-names which constitutes a documentary source without precedent. A second volume will soon be consecrated to the Amerindian sites discovered during the same operation.